Pengaruh Rata-Rata Curah Hujan Terhadap Kapasitas Infiltrasi Dan Stabilitas Tanah Di Wilayah Pertanian - Mendrofa, Putra Zato; Hulu, Yanuari (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze the effect of rainfall on infiltration capacity and soil stability in agricultural areas. Data on rainfall, infiltration capacity and soil stability were collected through direct measurements in the field using a rain gauge and infiltrometer, as well as soil aggregate stability tests in the laboratory. The research results show that high rainfall significantly reduces soil infiltration capacity and accelerates the disintegration of soil aggregates, especially in clay-textured soils. In the rainy season, infiltration capacity decreases by up to 50%, while soil aggregate stability decreases by around 40%. These findings indicate that high rainfall intensity increases the risk of erosion in agricultural areas and affects soil fertility in the long term. To overcome this problem, it is necessary to apply soil conservation techniques, such as planting cover crops and reducing tillage, to improve soil structure and reduce the rate of erosion. It is hoped that the results of this research can become a basis for farmers and policy makers in developing sustainable land management strategies.